Incidence and severity of cassava mosaic disease in the Republic of Congo - Ntawuruhunga, Pheneas; Okao-Okuja, G.; Bembe, A.; Obambi, M.; Armand Mvila, J.C.; Legg, James P. (2007)
Diagnostic surveys were conducted in 2002 and 2003 in order to provide a comprehensive and detailed assessment of the status of cassava mosaic disease (CMD) in the Republic of Congo (ROC) and to determine if the disease was spreading. In 2002, 105 farmers’ fields were assessed in the four major cassava-producing regions of the country. In 2003, 163 fields were sampled in nine regions and Brazzaville Commune. Incidence of cassava mosaic disease was generally high, averaging 80 and 86 % for 2002 and 2003, respectively; while damage was moderate to severe. In 2002, disease incidence was moderate in Pool (73%) but high in Brazzaville (81%), Cuvette Centrale (82%) and in Plateaux Region (84%). Pool region still had the lowest incidence (78%) in 2003, while Sangha (95%) had the highest incidence. The greatest disease severity was recorded in Niari region in the south and Cuvette Ouest region in the north in 2003. East African cassava mosaic virus Uganda variant (EACMVUG) occurred virtually throughout the country, commonly in dual infections with African cassava mosaic virus. The high incidence of disease in plants considered to be the results of cutting infection (74% in 2002 and 82% in 2003), relatively low incidence of disease in plants considered to be infected by whiteflies and wide distribution of EACMV-UG points to the fact that the CMD pandemic is a chronic in the country and the areas sampled are currently in a stable post-epidemic phase. This situation is comparable to that in areas of East Africa affected by a pandemic during the 1990s, including Uganda, parts of western Kenya and north-western Tanzania. These findings clearly verify the assertion that the CMD pendemic has expanded across Central Africa and provide a basis for designing interventions and control strategies for the entire region.